Prospects and Challenges of the Peer Teaching Approach in the Intermediate EFL Classrooms of Bangladesh - Mohammad Nazmul Haque Shikder Shiblu; Tamanna Akter; Samia Islam; Md Nasim Mahmud (Faculty of Education and Teacher Training of UIN Palopo, 2024)
The current study aimed to investigate the opportunities and challenges of utilizing the peer teaching approach at the intermediate level classrooms in the English as a foreign language (EFL) context of Bangladesh. The researchers employed a mixed-method approach to conduct this study. The study participants were 128 students and 15 teachers from five intermediate colleges in Bangladesh. The participants were selected through a convenience sampling technique. The researchers used two questionnaire surveys: the teacher questionnaire and the student questionnaire, to collect the study's quantitative data. A focus group discussion (FGD) was conducted with five experienced teachers to obtain in-depth information about the prospects and challenges of implementing the peer teaching approach and its policy implications. The study’s findings revealed positive perceptions of the approach at the intermediate EFL classrooms in Bangladesh to develop communication and presentation skills in the English language, learning attitude, lesson engagement, learners’ autonomy, peer feedback, etc. However, the most significant challenge to the effective implementation of peer teaching is the large class size of the institutions.